Increased medial meniscus extrusion on ultrasonography in highly competitive rugby players: A cross-sectional study - Kaoru Okano; Norimitsu Kinoshita; Ayame Matsuoka; Hiroaki Seto (PLoS ONE, 2026)
Medial meniscal extrusion (MME) has been shown to be associated with the onset and progression of knee osteoarthritis (KOA); however, evidence focusing on young athletes without a history of knee injury remains limited. This study aimed to determine whether MME is already increased in young competitive rugby players compared with controls. The participants comprised 94 male collegiate rugby players without a history of knee trauma or surgery (165 knees) and 42 male university students serving as controls (81 knees). MME was assessed bilaterally using ultrasonography (US) in three knee positions: supine, figure-4, and single-leg standing. Between-group comparisons were performed using linear mixed-effects models with group and side as fixed effects, body mass index as a covariate, and participant ID as a random effect. Estimated marginal means and corresponding 95% confidence intervals were derived from the models. p -values for the group effect were adjusted across knee positions using the Benjamini–Hochberg procedure. The rugby group exhibited significantly greater MME than the control group across all knee positions (all p < 0.001). Greater MME was observed in young rugby players even in the absence of clinically apparent knee injury. These findings suggest an association between participation in high-intensity rugby and increased MME, which may reflect early changes related to KOA. Early identification of these alterations provides an opportunity for timely intervention aimed at preserving long-term joint health in contact sport athletes. However, because this study was cross-sectional, causality cannot be inferred. US represents a practical method for evaluating meniscal behavior under weight-bearing conditions that reflect sport-specific loading characteristics, and future longitudinal and interventional studies are warranted to establish practical MME assessment approaches and effective KOA prevention strategies in rugby players.